ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN BIMA TAHUN ANGGARAN 2017- 2021 - Kumba Digdowiseiso; Muh Alfian (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the regional financial management performance of the Bima Regency Government. This type of research is descriptive research with a quantitative approach. The data analysis technique used is to calculate the ratio of effectiveness, the ratio of regional financial independence, the ratio of the degree of decentralization and the ratio of activity (Direct and Indirect Expenditures). The Effectiveness Ratio of Regional Original Income (PAD) for Bima Regency shows that the implementation of dominant regional taxes and fees is at a low level (below 100%) or ineffective. Based on the calculation of the Regional Financial Independence Ratio for Bima Regency from 2017 to 2021, the relationship pattern from 2017 to 2021 is entirely instructive with very low finances. The Activity Ratio shows that the ratio of indirect spending to total spending is still greater than the ratio of direct spending to total spending. The conclusion from the financial performance analysis of the Bima Regency Government for 2017-2021 has not run optimally as expected.